Effect of aging on machinability of 6061 aluminium alloy - Emir Izwandy, Dzulkafli (2010)
The main purpose of this project is to study the effect of aging on machinability of 6061 aluminium alloy and also to investigate the effect of variation aging time on machinability of 6061 aluminium alloy which has been heat treated to specific temperature. The effect investigated for the as received, solution heat treated (SHT) and solution heat treated with aged (SHTA) conditions during this study. The effect of different aging times which are 1 hour, 3 hours and 5 hours at 160°C and 200°C results the effect on the milling performances. The process that has been gone through the experiment are sample preparation, solution heat treated, aging at various times and temperatures, milling process, surface analysis, surface roughness and the Vickers hardness test. From the experiment, the sample is harder after gone through all the process. As the conclusion of all the experiments that have been done, the aging has affected the 6061 aluminium alloy in terms of the hardness, microstructure behaviour and the surface roughness of the specimens.